The The Prevalence and Factors Associated with Metabolic Syndrome in RheumatoidArthritis Patients - Rudy Hidayat (Indonesian Journal of Rheumatology, 2022)
Background: Rheumatoid arthritis (RA) is an independent risk factor ofcardiovascular disease (CVD), causing 30-50% mortality in RA patients.Metabolic syndrome is a combination of metabolic disorders that can bemanifested as central obesity, impaired blood pressure, or abnormalities ofcarbohydrate and lipid metabolism, which is closely associated with CVD inRA patients. The prevalence and factors associated with the incidence ofmetabolic syndrome in RA patients vary in previous studies. This studyaimed to determine the prevalence and factors associated with the incidenceof metabolic syndrome in RA patients at Cipto Mangunkusumo NationalCentral General Hospital, Jakarta. Methods: A total of 145 RA patients atthe Rheumatology Clinic of Cipto Mangunkusumo National Central GeneralHospital from October to December 2021 were included as research subjectsby consecutive sampling method. History taking about the disease anddemographic data, physical and anthropometric examination, andlaboratory tests were done on the patients. The prevalence of the metabolicsyndrome was determined using harmonization criteria. Statistical analysiswas performed to determine the association of the variables of age, smokinghabit, disease activity, duration of disease, glucocorticoid treatment, andmethotrexate treatment with metabolic syndrome in RA patients. Results:The prevalence of metabolic syndrome was 19.3% in RA patients with a mean age of 49.8 ± 11.6 years. The variables of gender, age, deformity, physical activity, extraarticular manifestation, smoking habit, disease activity,disease duration, glucocorticoid treatment, and methotrexate treatmentwere not statistically significant to the incidence of metabolic syndrome inRA patients. Conclusion: The prevalence of metabolic syndrome in RApatients in this study was 19.3%, and no variable was associated with theprevalence of metabolic syndrome.